Halbach array assisted assembly of orderly aligned nickel nanowire networks as transparent conductive films. (13th June 2019) - Wang, Jie; Liu, Shumin; Ban, Chaolei; Jia, Zhengfeng; He, Xiaohu; Ma, Jie; Pu, Xipeng; Li, Wenzhi; Zhi, Linjie
Abstract: The aspect ratio and arrangement of nanowires play an important role in achieving excellent optoelectronic performance for metal nanowire-based transparent conductive films (TCFs). However, limited to the technology and material properties, studies are always focused on only one of the issues. Here, a novel strategy for manipulating the relative aspect ratio and arrangement of nickel nanowires (NiNWs) at nanoscale by Halbach array assisted assembly technology is introduced. Head-to-tail nickel nanowire chains as large as hundreds of micrometers are formed as a result of the dipole–dipole interactions of wire–wire. The arrangement of nickel nanowires can be preciously controlled by layer-by-layer deposition. Notably, the alignment create a significant improvement on the optoelectronic performance of nickel nanowire TCFs. The optimized orderly aligned NiNWs TCFs demonstrate super optoelectronic performance (90 Ω sq −1, 86%) than disordered NiNW TCFs (200 Ω sq −1, 80%). Moreover, NiNW-based TCFs exhibit outstanding long-term oxidation stability at 80 °C over 30 d as well as high-temperature oxidization stability even up to 300 °C, that is the most stable metal nanowire-based TCFs in air as far as we know. The low-cost, good optoelectronic performance and excellent oxidation resistance of aligned NiNWs will make them as attractive alternatives to silver nanowires for TCFs application.